Effects on women empowerment of awareness raising - Vítor Jo\~ao Pereira Domingues Martinho (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This work is based on a project developed by the ACCIG (Association of the Culture and Knowledge for the Gender Equality) for some rural municipalities in the Center of Portugal. This project was financed by national funds and by funds from the European Union through the NSRF (National Support Reference Framework). The ACCIG aims to empower people, namely the more disadvantaged, particularly the women who are in more vulnerable situation. From the project, for this work, was used the information about the awareness raising. Namely, the information about what was did in these actions of sensitization, about the characterization of the participants in these initiatives and about the receptivity of the women for these projects. The principal objective of this project is to empower the more disadvantaged social groups, particularly women, enabling these persons to a more civic participation.
Keywords: O18; R00; Z13; 300; Women empowerment; rural municipalities; awareness raising